Contextual Teaching and Learning Based on HOTS and Pancasila Profile: Its Influence on Learning Interest in Islamic Religious Education - Ayuni Firasmita; Agus Fawait; Diah Kartika Sari (MUMTAZ : Jurnal Pendidikan Agama Islam, 2025)
Learning interest is one of the fundamental factors in learning. Conventional and monotonous learning causes low interest in learning among students. Efforts to overcome this by creating meaningful learning, namely applying contextual teaching and learning based on Higher Order Thinking Skills (HOTs) and the Pancasila profile. This study aims to determine the influence of HOTs-based contextual teaching and learning and the Pancasila profile on learning interest Islamic Religious Education at State Vocational High School 2 Bondowoso. Type of comparative causal research with a sample size of 69 students. Data were collected using validated research instruments. Data analysis used the independent sample t-test and simple linear regression analysis. The results show that the mean score for the CTL group was 64,53, while the mean score for the conventional group was 56,31, and the significance value of the regression analysis results 0,000<0,05, meaning that contextual teaching and learning based on HOTs and the Pancasila profile had a significant simultaneous influential on learning interest Islamic Religious Education in grade X at State Vocational High School 2 Bondowoso. These findings indicate students' ability to analyze material, connect it to relevant life experiences, and apply it in real life. Therefore, HOTs-based contextual learning and the Pancasila profile are proven to be effective in increasing learning interest Islamic Religious Education in vocational schools and supports the development of 21st century educational competencies..